(untitled) (Fiep Bulletin - online, 2015)
Introduction: The Flextest consists in a method of the maximum passive mobility evaluation of 20 articulate corporal movements and each one of the movements is measured in an increasing and discontinuous scale of entire numbers from 0 to 4, totalizing five possible values, whose analysis is qualitative, the zero (0) characterizes extreme hypomobility and the 4 hypermobility of subjective forms. The flexibility is recognized as one of the main components of the physical aptitude related to the health, however it still has much to advance in the area of measurement and evaluation of the movement amplitude. The kinematics angular analysis, through the processing of the Computerized Biophotogrametry, can be used to evaluate the movements of the Flextest. In this paper, it was chosen the trunk flexion movement in the Flextest by Biophotogrametry to express quantitatively the degree of flexibility in this movement, trying to identify values to an angular scale in the process of evaluation for the flextest. Objective: To establish relation among the degrees in the trunk flexion movement in the Flextest, and the measures obtained through the Biophotogrametry angular analysis. Method: participated in the research 37 students with 8 to 11 years old. It was realized through a patient’s card of anamnesis, evaluation of the flexibility of the trunk flexion movement through the Flextest, and the captivation of photographic images until the angular photo interpretation. Results: The numerical intervals obtained by the Biophotogrametry for the trunk flexion movement of the Flextest in the group in study were: 47,28 in the Flextest graduation 1; 52,15 to graduation 2; and 62,97 to graduation 3. Graduation 0 and 4 were not possible to calculate due to the fact that they are very rare. Conclusion: it can be concluded that the Biophotogrametry can be used as a resource to evaluate the trunk flexion movement, considering that is necessary to realize some improvement.